2020
DOI: 10.1177/1097184x20976730
|View full text |Cite
|
Sign up to set email alerts
|

Man Made Beautiful: The Social Role of Grooming and Body Work in Performing Middle-aged Corporate Masculinity in South Korea

Abstract: This article examines how middle-aged urban men in South Korea relate to age-relevant ideas of beauty in a society in which youthful muscular bodies are increasingly presented as the ideal or, arguably, even as a norm. Drawing on in-depth interviews with 13 male participants aged 36–56 years residing in the Seoul metropolitan area, it seeks to outline what role grooming and aesthetic labor play in their everyday social interactions. The findings suggest that men’s aesthetic practices in the workplace are stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…The findings showed no difference by gender insofar as the desire for surgery was concerned, which resonates with Elfving‐Hwang's (2021) recent study that shows how Korean men (not merely women) are pressured to attain to contemporary beauty ideals. It may be, however, that men and women experience different kinds of coercive pressure or different uses of erotic capital, which deserves closer scrutiny by future research beyond the scope of this study.…”
Section: Methodssupporting
confidence: 75%
See 2 more Smart Citations
“…The findings showed no difference by gender insofar as the desire for surgery was concerned, which resonates with Elfving‐Hwang's (2021) recent study that shows how Korean men (not merely women) are pressured to attain to contemporary beauty ideals. It may be, however, that men and women experience different kinds of coercive pressure or different uses of erotic capital, which deserves closer scrutiny by future research beyond the scope of this study.…”
Section: Methodssupporting
confidence: 75%
“…Although this is traditionally seen as a gendered phenomenon affecting largely women, Elfving‐Hwang (2021) recently finds in her study of middle‐aged urban men in South Korea that men are also coerced into aesthetic labour, such as extensive grooming and striving for young muscular bodies, to favourably soothe power relations, especially in white‐collar work. The coercive pull towards the micro‐level cultural phenomena of cosmetic surgery and barter of advantages within sexual fields across genders thus hearkens to their structuration not only by cultural associations (Shilling, 2022a, 2022b), but by macro‐level economic anxieties.…”
Section: Rationalising the Consumption Of Embodied Goods: Risk Networ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, other research has suggested that, while Koreans have highly negative views about fat bodies, they do not stigmatize fat people (Sun, as cited in Anderson‐Fye, 2018; Monocello, 2020). Fatness is a negative bodily trait that sufficient effort in other areas, like fashion choices and other forms of self‐maintenance (Elfving‐Hwang, 2021), can mitigate, ultimately positioning fatness as relatively less important despite it being unattractive.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, men with big muscles were often viewed as pathologic, undereducated, and having misplaced priorities, a feeling shared by older Korean men as well (Elfving-Hwang 2021 ). While their bodies were admired—mostly by other men—these same admirers had little interest in pursuing these bodies for themselves.…”
Section: Discussionmentioning
confidence: 99%